Perancangan dan Implementasi Aplikasi E-Commerce Berbasis Android pada UMKM Radeaa-Store - Rhoma Rajani Saragih; Shufiana Shufiana; Fatma Ulfiana; Novita Asrif Siregar; Hauzatul Aina (CV. ALIM'SPUBLISHING, 2026)
The development of information technology encourages MSMEs to utilize digital systems to improve operational effectiveness and customer servise. Radeaa Store as an MSMEs operating in the fashion selector still faces obstracles in managing products, transactions and preparing reports which are carried out conventionally. This research aims to design and implement an Androidbased e-commerce application to support the digitalization of business processes at Radea-Store. The system development method used is waterfall which consists of planning stages, need analysys, design, implementation and testing. The application was developed using Flutter for mobile, Laravel for the web admin dashboard, and Midtrans as a payment gateway. The research results show that the application is successful in providing product, order, customer, sales, report, and online payment management features. Based on black box testing, all main features work according to system requirements. This application is able to increase operational efficiency and provide easy transactions for customers and MSME managers.